Hospitalisations from 1 to 6 Years of Age: Effects of Gestational Age and Severe Neonatal Morbidity. Issue 3 (2nd April 2015) - Stephens, Alexandre S.; Lain, Samantha J.; Roberts, Christine L.; Bowen, Jennifer R.; Simpson, Judy M.; Nassar, Natasha
Abstract Background To investigate whether the adverse infant health outcomes associated with early birth and severe neonatal morbidity (SNM) persist beyond the first year of life and impact on paediatric hospitalisations for children up to 6 years of age. Methods The study population included all singleton live births, >32 weeks gestation in New South Wales, Australia, in 2001–2005, with follow‐up to 6 years of age. Birth data were probabilistically linked to hospitalisation data (n = 392 964). The odds of hospitalisation, mean hospital length of stay (LOS) and costs, and cumulative LOS were evaluated by gestational age and SNM using multivariable analyses. Results A total of 74 341 (18.9%) and 41 404 (10.5%) infants were hospitalised once and more than once, respectively. SNM was associated with increased odds of hospitalisation once (adjusted odds ratio [aOR] 1.16 [95% confidence interval 1.10, 1.22]) and more than once [aOR 1.51 (1.43, 1.61)]. Decreasing gestational age was associated with increasing odds of hospitalisation more than once from aOR 1.19 at 37–38 weeks to 1.49 at 33–34 weeks. Average LOS and costs per hospital admission were increased with SNM but not with decreasing gestational age. Cumulative LOS was significantly increased with SNM and decreasing gestational age. Conclusions Adverse effects of SNM and early birth persist between 1 and 6 years of age. Strategies to prevent early birth and reduce SNM, and to increase health monitoring of vulnerable infants throughout childhood may help reduce paediatric hospitalisations.